Comparative analysis of the efficacy of vaccines using structural protein subunits of the severe fever with thrombocytopenia syndrome virus - Kim, Sohee; Jeon, Kyeongseok; Choi, Hooncheol; Jeong, Da-Eun; Kang, Jun-Gu; Cho, Nam-Hyuk (Frontiers in Microbiology, 2024)
The Severe Fever with Thrombocytopenia Syndrome virus (SFTSV) represents a significant emerging health threat as a tick-borne pathogen that causes SFTS, with mortality rates ranging between 10% and 30%. Despite the considerable risk presented by SFTSV, an effective vaccine has yet to be developed.Our study assessed the efficacy of recombinant protein vaccines, focusing on the purified nucleocapsid protein (NP) and surface glycoproteins (Gn and Gc), against SFTSV in both singular and combined formulations. Individual vaccinations with NP or Gn subunits yielded partial protection in type I interferon receptor-knockout (IFNAR-KO) mice, with survival rates of 66.7% and 16.7%, respectively, whereas Gc vaccination did not confer significant protection, resulting in 100% mortality similar to that of the unvaccinated control group. Notably, NP vaccination substantially enhanced antigenspecific T cell responses, and Gc vaccination exhibited strong neutralizing activity against SFTSV.Among the combined recombinant protein formulations (Gn+NP, Gc+NP, and Gn+Gc+NP) tested, the Gc+NP combination provided the highest survival rate (85.7%) following challenge with a lethal dose of SFTSV, highlighting its potential as a vaccine candidate. Longitudinal studies showed that antibody levels in both wild type C57BL/6 and IFNAR-KO mice peaked between 2 and 3 months postvaccination and declined over time. A notable decrease in NP-specific CD8 + T cell responses was observed six months post-vaccination in C57BL/6 mice, while NP-specific CD4 + T cell responses persisted up to 12 months. By 12 months post-vaccination, all IFNAR-KO mice vaccinated with single subunit antigens succumbed to the virus, suggesting that effective protection against SFTS may rely on antibody responses to subunit antigens and/or CD8 + T cell activity. These findings underscore the necessity of an optimized SFTS vaccine that combines protective antigens with an adjuvant system to ensure durable humoral and cellular immunity.